Eruptive cutaneous squamous cell carcinoma and psoriasis: response to cetuximab. (23rd April 2014) - Kamaria, M.; Shea, C. R.; Chin, R. K.; Cohen, E. E.; Maggiore, R.; Bolotin, D.
Summary Cutaneous squamous cell carcinomas (CSCCs) comprise 20–30% of nonmelanoma skin cancers (NMSCs), and continue to increase in incidence. We report a case of a patient with severe psoriasis who had recurrent and eruptive CSCCs on her leg, which were successfully treated with cetuximab and radiotherapy. The patient had successful long‐term clearance of her skin tumours, with the additional finding of resolution of psoriasis while on cetuximab therapy.